Pengaruh Parameter Pemotongan Dan Nose Radius Pahat Insert W-Style Pada Pembubutan Baja S45c - Henry Widya Prasetya; Hari Boedi Wahjono (Virtual of Mechanical Engineering Article, 2020)
In the manufacturing industry, the cutting process, especially lathes, has developed rapidly, one of which is in the rail transportation industry sector. The purpose of this study was to determine the effect of cutting parameters and the nose radius of the W-style insert tool on the level of surface roughness in the turning process of S45C steel. This research uses experimental research methods. In this study, using a variation of cutting parameters and nose radius. Variations in cutting parameters using cutting speeds of 195 Rpm, 300 Rpm and 440 Rpm. Variation of the depth of cut 1 mm and 2 mm. Variation of feed speed 0.1 mm / rev, 0.2 mm / rev and 0.3 mm / rev. While the variation of the nose tool radius for inserting W-style is 0.4 mm and 0.8 mm. After turning the surface roughness test was carried out using the Surface Roughness Tester. The results of this study indicate that the increasing cutting speed and nose radius of the insert tool, decreasing feeding velocity and cutting depth results in good surface quality. Keyword: W-series insert tool, nose radius, surface roughness.